2019
DOI: 10.1093/carcin/bgz029
|View full text |Cite
|
Sign up to set email alerts
|

Potential functional variants in SMC2 and TP53 in the AURORA pathway genes and risk of pancreatic cancer

Abstract: The AURORA pathway participates in mitosis and cell division, and alterations in mitosis and cell division can lead to carcinogenesis. Therefore, genetic variants in the AURORA pathway genes may be associated with susceptibility to pancreatic cancer. To test this hypothesis, we used three large publically available pancreatic cancer genome-wide association study (GWAS) datasets (PanScan I, II/III and PanC4) to assess the associations of 7168 single nucleotide polymorphisms (SNPs) in a set of 62 genes of this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…Although seven SNPs of TP53 (i.e., rs17884306, rs17879377, rs9891744, rs75732100, rs9895829, rs17883323, and rs8079544) located at 17p13 have been previously reported by the AURORA pathway‐based analyses,Query Deleted, the TP53 rs35850753 and other eight SNPs (i.e., MAP2 rs35075084, PRKAG2 rs2727572, rs12668489, rs2538046 and rs34852782 and RPTOR rs62068300, rs17848685 and rs3751936) located at 2q34, 7q36.1, and 17q25.3, respectively, are novel findings, for which we performed additional in silico analysis for their functional relevance. The results of these SNPs in each of GWAS datasets and the final meta‐analysis are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Although seven SNPs of TP53 (i.e., rs17884306, rs17879377, rs9891744, rs75732100, rs9895829, rs17883323, and rs8079544) located at 17p13 have been previously reported by the AURORA pathway‐based analyses,Query Deleted, the TP53 rs35850753 and other eight SNPs (i.e., MAP2 rs35075084, PRKAG2 rs2727572, rs12668489, rs2538046 and rs34852782 and RPTOR rs62068300, rs17848685 and rs3751936) located at 2q34, 7q36.1, and 17q25.3, respectively, are novel findings, for which we performed additional in silico analysis for their functional relevance. The results of these SNPs in each of GWAS datasets and the final meta‐analysis are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…By combining a meta-analysis with the largest genome-wide association (GWA) meta-analysis datasets, Kar et al (2016) found that SMC2 is associated with susceptibility to breast and ovarian cancer. Feng et al (2019) used genome-wide association studies (GWASs) of pancreatic cancer datasets and found that the expression level of SMC2 mRNA in human pancreatic cancer tissues was significantly higher than that in adjacent non-neoplastic pancreatic tissues. Davalos et al (2012) found that SMC2 is a direct transcriptional target of the WNT signaling pathway, and experimental results showed that the down-regulation of SMC2 expression can inhibit WNT-activated cell proliferation; therefore, SMC2 could be used as a novel target for therapeutic interventions for tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary clinical studies have been conducted to validate the e cacy and safety of Aurora kinase inhibitors in AML [47][48][49]. Although the association of TP53 mutation and AURKA expression has been rarely studied previously for AML, it was explored in solid tumors with high frequency of TP53 variants, including adrenocortical carcinoma [50], pancreatic cancer [51], head and neck cancer [52], hepatocellular carcinoma [53] and ovarian cancer [54]. Moreover, in cancer cell lines lacking p53, resulting from genetic engineering to express HPV16-E6 oncoprotein or siRNA targeting TP53, the inhibitor of Aurora kinases (VX680) induced apoptosis was enhanced in comparison with cell lines with wide-type p53 [55].…”
Section: Discussionmentioning
confidence: 99%